2021
DOI: 10.1161/jaha.120.019988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of First‐Pass Reperfusion on Outcome After Endovascular Treatment for Ischemic Stroke

Abstract: Background First‐pass reperfusion (FPR) is associated with favorable outcome after endovascular treatment. It is unknown whether this effect is independent of patient characteristics and whether FPR has better outcomes compared with excellent reperfusion (Expanded Thrombolysis in Cerebral Infarction [eTICI] 2C‐3) after multiple‐passes reperfusion. We aimed to evaluate the association between FPR and outcome with adjustment for patient, imaging, and treatment characteristics to single out the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
1
17
1
Order By: Relevance
“…The association between FPR and 24-hour NIHSS is comparable to our results in patients with anterior circulation ischemic stroke (compared with no FPR; −45% vs −37% compared with MPR −14% vs −23%). 12 In contrast to patients with anterior circulation ischemic stroke, in patients with PCS there is no significant benefit of FPR over MPR in our results. In a previous study with a pooled analysis of patients with either anterior or posterior circulation stroke, no differences in outcome (dichotomized mRS) between the FPR and MPR group were noted.…”
Section: Discussioncontrasting
confidence: 76%
“…The association between FPR and 24-hour NIHSS is comparable to our results in patients with anterior circulation ischemic stroke (compared with no FPR; −45% vs −37% compared with MPR −14% vs −23%). 12 In contrast to patients with anterior circulation ischemic stroke, in patients with PCS there is no significant benefit of FPR over MPR in our results. In a previous study with a pooled analysis of patients with either anterior or posterior circulation stroke, no differences in outcome (dichotomized mRS) between the FPR and MPR group were noted.…”
Section: Discussioncontrasting
confidence: 76%
“…In the MR CLEAN Registry, an association was found between a higher EXPno and increased probability for first pass reperfusion. Additionally, first pass reperfusion itself was associated with an increased probability of good clinical outcome 5…”
Section: Discussionmentioning
confidence: 99%
“…While a previously performed MR CLEAN Registry sub-study focused on the effect of the number of passes on functional outcome and found that first-pass reperfusion was associated with favorable functional outcome,25 we went one step further and compared single pass good reperfusion with multiple pass excellent/complete reperfusion. In line with a previous descriptive analysis,6 we found that if three or more passes were necessary to achieve excellent/complete reperfusion, functional outcome was not better compared with good reperfusion in a single pass.…”
Section: Discussionmentioning
confidence: 99%